The Structure, Activation and Signaling of IRE1 and Its Role in Determining Cell Fate - Siwecka, Natalia (Biomedicines, 2021)
Inositol-requiring enzyme type 1 (IRE1) is a serine/threonine kinase acting as one of three branches of the Unfolded Protein Response (UPR) signaling pathway, which is activated upon endoplasmic reticulum (ER) stress conditions. It is known to be capable of inducing both pro-survival and pro-apoptotic cellular responses, which are strictly related to numerous human pathologies. Among others, IRE1 activity has been confirmed to be increased in cancer, neurodegeneration, inflammatory and metabolic disorders, which are associated with an accumulation of misfolded proteins within ER lumen and the resulting ER stress conditions. Emerging evidence suggests that genetic or pharmacological modulation of IRE1 may have a significant impact on cell viability, and thus may be a promising step forward towards development of novel therapeutic strategies. In this review, we extensively describe the structural analysis of IRE1 molecule, the molecular dynamics associated with IRE1 activation, and interconnection between it and the other branches of the UPR with regard to its potential use as a therapeutic target. Detailed knowledge of the molecular characteristics of the IRE1 protein and its activation may allow the design of specific kinase or RNase modulators that may act as drug candidates.